A winged solar biomass reactor for producing 5-hydroxymethylfurfural (5-HMF). (April 2021) - Li, Qiyuan; Zhuo, Yuting; Shanks, Katie; Taylor, Robert A.; Conneely, Brendan; Tan, Angelina; Shen, Yansong; Scott, Jason
Graphical abstract: Highlights: A new 'winged' solar concentrator was developed to enable biomass conversion at 150 °C. An evacuated solar tube was placed at the focal line to serve as a biomass reactor. The wings boosted the thermal efficiency of the design from 18% to 25% at 150 °C. The 'on-sun' 5-HMF yield was 21 mol % from a sucrose source in the biomass reactor. A CFD model was developed to investigate the thermochemical behaviours of the reaction. Abstract: Biomass-derived alcohols such as 5-Hydroxymethylfurfural represent a promising intermediary energy and species carriers for hydrogen and value‐added chemical production. Solar-driven reforming of biomass to 5-HMF at the desired reaction condition (e.g., at 150 °C and 5 bars) offers a sustainable route, but the lack of a rooftop-based solar biomass reactor represents a substantial impediment. In this work, a unique, low-profile "winged" solar concentrator with an evacuated tube reactor was designed for the renewable production of 5-HMF. The viability of this design was examined in detail, using sucrose as the feedstock for 5-HMF production in the presence of sulfuric acid. The optical study indicated that the winged structure significantly increased the effective concentration ratio (by 42%) and that the design has a broader acceptance angle (from 60° to 90°) compared to CPC alone. During outdoor experiments, the wings boosted the thermal efficiency from 18% to 25% when operating at 150 °C, and achieved a maximum 5-HMF yield of 21 mol % (under a solar irradiance of 800 W/m 2 ). In parallel, a transient computational fluid dynamics model was developed to further elucidate the heat and mass transfer phenomena inside the reactor and to investigate a broader range of operating conditions and reactor design parameters. The numerical and experimental results were in agreement that a specific energy consumption for 5-HMF production of 23 kWh/kg was achievable and that a full-scale system ( 3 L reactor volume, 2.1 m 2 gross area) can produce 0.45 kg of 5-HMF per day, with an average daily solar input of 5 kWh/m 2 .